Iodine status, and knowledge about iodine deficiency disorders in adolescent school girls aged 14-19 years, 2016 - Zahra Heidari; Seyed Rafie Arefhosseini; Mehdi Hedayati; Elnaz Vaghef-Mehrabany; Mehrangiz Ebrahimi-Mameghani (Tabriz University of Medical Sciences, 2019)
Background: Adequate iodine intake by women in child-bearing age affects fetus neurodevelopment during pregnancy. A majority of previous studies has investigated iodine status among children, and there is limited data on female adolescents who are more exposed to consequences of iodine deficiency (ID) in their near-future pregnancies; thus, we aimed to assess iodine status, and knowledge on iodine deficiency disorders (IDDs) among adolescent school girls (14-19 years old) in Shahriar, Iran. Methods: This cross-sectional study was conducted among 223 female students selected through multi-stage cluster sampling from 12 schools. Iodine and creatinine concentrations were measured in casual urine samples. Iodine content of household salts was also assessed.Data on intake of salt and iodine-rich food sources were collected applying a food frequency questionnaire (FFQ), and knowledge about iodine and IDDs were assessed by a questionnaire. Results: Median and Mean (95% CI) concentrations of urinary iodine and creatinine were 129 µg/L, 137.62 µg/L (95% CI: 126.28, 148.95) and 1.72 g/L, 1.86 g/L (95% CI: 0.55-3.17),respectively. The frequency of mild, moderate and severe ID were 22.4%, 14.3% and 0%,respectively; 43.5% had adequate, and 3.1% had excessive urinary iodine levels. Mean saltiodine concentration was 21.69 (SD=10.56) ppm. Mean knowledge score was 12.7 (SD=3.44).About half of the students had a poor (25.1%) or fair (24.2%) knowledge about iodine deficiency.Adjusting for the confounders, no significant positive association was found between knowledge about iodine-rich food sources and goitrogens with urinary iodine excretion. Conclusion: Adolescent girls in Shahriar had relatively poor knowledge of iodine, and about one third of them suffered from ID.